Nano-Green Betel Leaf Extracts (Piper betle L.) Inhibits the Growth of Streptococcus mutans and Staphylococcus aureus - Florenly Florenly; Novelya Novelya; Mizeli Janiar; Miranda Miranda; Le Quang Phan Dang Hai; Phan Minh Quang (e-GiGi, 2022)
Abstract: Streptococcus mutans is a type of bacterium that initiates plaque formation on the tooth surface causing tooth decay, meanwhile, Staphylococcus aureus causes pyogenic infections such as abscesses to necrosis. Green betel leaf (Piper betle L.) contains secondary meta-bolites that have the potential as antibacterial. This study aimed to investigate the effectiveness of green betel leaf extract (Piper betle L.) in micro and nano sizes against Streptococcus mutans and Staphylococcus aureus. This was an experimental and laboratory study with a post-test-only design. The results showed that nano-green betel leaf extracts had antibacterial activity against Streptococcus mutans and Staphylococcus aureus. Green betel leaf extract had a much larger inhibition zone against Staphylococcus aureus rather than against Streptococcus mutans in all groups (p<0.05), with inhibitory diameters of 13,883±1.1496 mm (micro 10%), 16,767± 1.8779 mm (micro 30%), and 18.667±3.148 mm (nano), respectively. A stable increase in antibacterial activity was derived from micro-green betel leaf extracts (Piper betle L.) concentrations of 10%, 30%, and nanoparticle size. In conclusion, nano-green betel leaf extract (Piper betle L.) showed better antibacterial effectiveness than micro-sizes in inhibiting Streptococcus mutans and Staphylococcus aureus bacteria.Keywords: Piper betle L.; nanoparticles; antibacterial; Streptococcus mutans; Staphylococcus aureus